Hospital patient safety grades may misrepresent hospital performance. Issue 2 (13th January 2014) - Hwang, Wenke; Derk, Jordan; LaClair, Michelle; Paz, Harold
<x xml:space="preserve">Abstract</x> Nationally, there is strong interest in measuring hospital performance in patient safety. The Leapfrog Group uses a survey, along with other data sources, to calculate patient safety scores for 2600 hospitals across the United States. Under this methodology, every hospital is assigned 1 of 5 letter grades (A, B, C, D, F) depending on how the hospital stands in safety performance relative to all other hospitals. The results have been widely marketed and disseminated to employers, payors, and the public. Leapfrog strongly encourages employers and payors to negotiate hospital reimbursement rates based on the safety grade the hospital receives. Leapfrog's effort to develop a standardized method to provide patient safety information should be commended. However, less than one‐half of the 2600 hospitals participated in the Leapfrog survey. For those nonparticipating hospitals, certain safety measures were absent and alternative measures were used to calculate the safety score. A sample of the nation's most prestigious hospitals (n = 35) was drawn from the U.S. News & World Report's "Best Hospitals." Overall, the group of participating hospitals (n = 18) received an average grade of A (mean safety score = 3.165), whereas the group of nonparticipating hospitals received an average grade of B (mean safety score = 3.012). These nonparticipating hospitals were rescored using the methodology for participating hospitals. The results show that the majority of nonparticipating hospitals would have received a better safety grade. This demonstrates a potential shortcoming of Leapfrog's method and its tendency to discriminate against nonparticipating hospitals. Journal of Hospital Medicine 2014;9:111–115. © 2014 Society of Hospital Medicine